Corporate Social Responsibility Perceptions on Purchase Intention: The Mediating Role of Country of Origin Image - Heny Hendrayati, Rahmy Karimah Syahidah, Sidra Ramzan ,Mochamad Achyarsyah (International Journal of Advanced Science and Technology, 2020)
Present study, analysis about the perspective of Corporate Social Responsibility (CSR) in Indonesian consumers’ view that may influence their buying interest on Chinese mobile phone. The study is also examined the relationship of Country of Origin Image as a mediation variable. Study analysis relies on data from total sample of 200 valid responds. The model has been tested using SPSS and applying the technique of Process Macro. The results indicate that the CSR perceptions has no relationship with the purchase intention. Therefore, Country of Origin Image mediated between them. Finally, the current study offers valuable empirical insights into the effects of the consumer’s CSR perception and Country of Origin image (especially with reference to a developing country perspective) on purchase intention.